Survival following disease recurrence of primary localized alveolar rhabdomyosarcoma. Issue 8 (15th February 2013) - Dantonello, Tobias M.; Int‐Veen, Christoph; Schuck, Andreas; Seitz, Guido; Leuschner, Ivo; Nathrath, Michaela; Schlegel, Paul‐Gerhardt; Kontny, Udo; Behnisch, Wolfgang; Veit‐Friedrich, Iris; Kube, Stefanie; Hallmen, Erika; et al.
Abstract Background Recurrences in primary localized alveolar rhabdomyosarcoma (RMA) are common. Post‐relapse survival is poor. We evaluated prognostic factors including relapse treatment in patients with recurrent RMA. Methods Relapses occurred in 115/235 patients with nonmetastatic RMA treated in four consecutive CWS‐trials after achievement of a complete remission. Sufficient information about post‐relapse treatment and outcome could be obtained in 99 patients and was retrospectively analyzed. Results Nine of 99 patients received no salvage therapy and died after a median of 2 months. The remaining 90 patients received multimodal relapse treatment including mandatory chemotherapy. Recurrences were grossly resected in 39 patients; 57 patients received radiation. At a median follow‐up from relapse of 8 years, 20 patients were alive and disease‐free (5‐year post‐relapse survival [PROS] 21.3 ± 8). All surviving patients apart from a single individual had an isolated, circumscribed recurrence. Sixteen of 20 survivors were treated with adequate local relapse therapy (ALRT, i.e., either complete resection or gross resection + radiation). Survival in the subgroup of 27 individuals with circumscribed recurrences and ALRT was significantly better (PROS 53.7 ± 19) compared with disseminated recurrences and/or tumors treated without ALRT. Absence of primary lymph node involvement, circumscribed relapses, ALRT, and achievement of a second CR were identified as independent favorable risk factors. Conclusion Post‐relapse survival for primary localized RMA is generally poor. However, certain patient groups differed significantly in their likelihood of survival and 50% of patients with circumscribed relapses treated with ALRT survived. These findings may form the basis for an evidence‐based risk‐stratification for recurrent disease including relapse treatment. Pediatr Blood Cancer 2013;60:1267–1273. © 2013 Wiley Periodicals, Inc.